Companies’ ESG performance under soft and hard regulation environment - Bence Lukács; Péter Molnár (Discover Sustainability)
Abstract The growing integration of Environmental, Social, and Governance (ESG) factors into corporate decision-making and investment strategies has heightened the need for reliable and comparable ESG ratings. However, substantial divergence across rating agencies—driven by inconsistent methodologies, weighting schemes, and disclosure practices—poses challenges for investors, firms, and regulators. Addressing a key gap in the literature, this study investigates how regulatory environments influence ESG rating divergence by comparing hard, soft, and unregulated frameworks across five major economies: the United States, China, Japan, Germany, and India. ESG ratings were collected from Sustainalytics, S&P Global, and Refinitiv for the top 50 publicly listed companies in each country. The divergence was measured using absolute score differences between agencies, and statistical tests and cluster analysis were conducted to evaluate the impact of regulation on rating consistency. The results indicate that countries with strong, mandatory ESG disclosure regimes—such as Germany's CSRD and India’s BRSR—exhibit significantly lower levels of rating divergence, while unregulated markets like the USA and China display the highest discrepancies. Notably, Japan’s soft-law approach achieves alignment levels comparable to those of hard-law environments, emphasizing the role of regulatory enforcement. These findings reinforce both signaling and agency theories by demonstrating how regulatory oversight and transparency reduce information asymmetry and promote stakeholder trust. The study highlights the importance of direct supervision of ESG rating agencies and supports global harmonization of ESG disclosure standards as a means to enhance market efficiency and comparability.